PENGARUH KUALITAS PRODUK, HARGA DAN IKLAN TERHADAP LOYALITAS PELANGGAN SHAMPO SUNSILK (STUDI KASUS PADA MAHASISWA PEREMPUAN DI FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS DIPONEGORO SEMARANG) - Jayanti, Emma Nur; Hermani, Agus; Nurseto, Sendhang (Jurnal Ilmu Administrasi Bisnis, 2015)
This research is motivated by the level of competition in the business field in Indonesia that is more getting strict in this globalization era. One product that has been competed by the manufacturer in this era is the woman’s shampoo product. Sunsilk Shampoo It had become first rank in the Top Brand Index (TBI) in Indonesia since 2010 until 2011. However, in 2012 until 2014, Sunsilk had not been longer at the first rank and the percentage was continously decline. If the declination is not immediately fixed, then Sunsilk shampoo will be fall down. Wherefore, there are so many brands of shampoos on the market that are most likely to shift the position of Sunsilk popularity in Indonesia nowadays.This research aims to detect the influence of product quality, price, advertising for Sunsilk shampoo’s customer loyalty. This type of research is explanatory, within collecting data through questionnaires and interviews. The sampling technique used purposive sampling technique. The sample amounted to 96 people who are female students users of Sunsilk shampoo at Faculty of Public Health Diponegoro University, Semarang. This research used a qualitative analysis and quantitative analysis technique. Quantitative analysis uses validity, reliability test, correlation coefficient, simple and multiple regression analysis, coefficient of determination, significance test (t test and F test).The results of this analysis showed that the variable of product quality, price and advertisement has a positive and significant effect partially for customer loyalty. Three variables were analyzed partially and simultaneously, the coefficient of the variable of product quality is greater than the other two variables. From three variables also obtained the result that the variable of product quality has greatest influential on customer loyalty of Sunsilk shampoo users. It was 0.583, while the price variable about 0.217 and 0,215 for advertising variables. While the coefficient of determination (R2) from variable of product quality, price and advertisement toward variable of customer loyalty was 36.2%. It meant that 36.2% of variable of customer loyalty can be explained by these three variables, while the remaining 63.8% is explained by other variables.Suggestions in this research is Sunsilk shampoo should improve the quality of their products function in order to their hair problems can be overcome well and not make new hair problems, create an aroma for all variants so that more visible the special of Sunsilk shampoo, increase the durability of Sunsilk shampoo’s aroma that could be durable more than one day, and increase the clarity of message from the advertisement by creating the short slogans but has clear meaning from the message conveyed in order to Sunsilk shampoo can stick out in the competition as today.